Association of High-Sensitivity C-Reactive Protein and Serum Malondialdehyde with Coronary Artery Disease Severity: A Cross-Sectional Study - Hashmat Ullah Khan, Masud Ali Ansari, Asma Hameed, Faroz Khan, Shafique Ahmed, Saifullah, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Coronary artery disease (CAD) remains a leading cause of morbidity and mortality worldwide. Inflammatory and oxidative stress biomarkers have emerged as potential indicators of atherosclerotic burden. High-sensitivity C-reactive protein (hs-CRP), a marker of systemic inflammation, and malondialdehyde (MDA), a byproduct of lipid peroxidation, may provide valuable insights into the severity of CAD. Aims and Objectives: The aims and objectives of present study was to evaluate the association of serum hs-CRP and MDA levels with the angiographic severity of CAD in patients undergoing coronary. angiography. Methodology: In this hospital-based cross-sectional study, 100 patients diagnosed with CAD at a tertiary cardiac center in Pakistan between May 2022 and May 2023 were enrolled. Serum levels of hs-CRP and MDA were measured using ELISA and spectrophotometric methods, respectively. Coronary angiography was performed, and disease severity was quantified using the Gensini scoring system. Patients were categorized into mild, moderate, and severe CAD groups. Correlations between biomarker levels and disease severity were analyzed using Spearman’s rank correlation and multivariate regression analysis to adjust for confounders. Results: Both hs-CRP and MDA levels were significantly elevated in patients with moderate and severe CAD compared to those with mild disease (p < 0.001). A strong positive correlation was observed between hs-CRP and Gensini score (r = 0.64, p < 0.001) as well as MDA and Gensini score (r = 0.58, p < 0.001). Multivariate analysis confirmed that elevated hs-CRP and MDA independently predicted higher CAD severity. Conclusion: Elevated hs-CRP and MDA levels are significantly associated with increased severity of coronary artery disease, underscoring their potential role as non-invasive biomarkers for risk stratification in clinical settings. Keywords: Coronary artery disease, hs-CRP, malondialdehyde, oxidative stress, inflammation, atherosclerosis, Gensini score.